Deterytorializacja ciała versus podmiotowość. „Inny” Jurija Mamlejewa - Przybysz, Anna Katarzyna (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The aim of this article is to emphasize the main character’s struggle with her own subjectivity. The author of the present paper tries to show that the events in the girl’s life affect her attitude to her own body. The variability in the relationship me and my body is perceived as one of the stages of acquiring self-awareness.